Kepemimpinan Transformasional dan Adaptif dalam Kelembagaan PAI untuk Menghadapi Tantangan Perubahan Pada Lembaga Pendidikan Tingkat Dasar - Shofwatin Sri Rahayu, Moh. Nasrul Amin (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to conduct an in-depth and systematic examination of the integration between transformational leadership and adaptive leadership within the institutional context of Islamic Religious Education (IRE) at the elementary level. The study employs a qualitative approach using a literature review method, analyzing relevant scientific literature, including leadership theories, educational policies, and previous research findings. The findings indicate that transformational leadership plays a crucial role in establishing vision, inspiration, and a values-based culture within the IRE institutional framework, while adaptive leadership is necessary for navigating social change, addressing undefined challenges, and fostering institutional flexibility. The integration of the two models produces a strategic and responsive leadership pattern that not only drives innovation but also strengthens organizational resilience in facing the dynamics of modern education. The implication is that this transformational-adaptive leadership model can be a strategic alternative in strengthening the governance of PAI institutions and serve as a reference for the development of policies and training in Islamic educational leadership oriented toward sustainability and institutional quality.